INTERAÇÕES ENTRE LEPIDÓPTEROS-PRAGA DA SOJA E ENTOMOPATÓGENOS, COM ÊNFASE EM BACILLUS THURINGIENSIS QUE EXPRESSA A PROTEÍNA CRY1AC - Wisch, Lucas Nataniel (2016)
Soybean is the main crop of economic importance and commercially produced on a large scale in Brazil. Nevertheless many are the factors that affect the productive potential of this oilseed, among them stand out the insects of the order Lepidoptera. As an alternative to control these pests, many growers have adopted the use of Bt soybean, which expresses the Cry1Ac toxin. However, the large area with this technology can generates a main concern that is Cry1Ac exposure to target and non-target insects and its entomopathogens, such Metarhizium rileyi and nuclear polyhedrosis virus. The aim of this study were to elucidate the HD-73 impacts, that expresses Cry1Ac, i) in the immune system of S. frugiperda in order to investigate whether Bt challenge parental induce "immune priming or transgenerational effects"; ii) on virulence and occlusion body yield in Spodoptera frugiperda iii) level of larval mortality of the noctuid species when applied simultaneously or sequentially with NPV and M. rileyi; and iv) the biological parameters of the noctuid species, when exposed in conjunction with entomopathogens. In the immune assay, neonate larvae were exposed ad libitum to different concentrations of HD-73 (0, 15, 33, 72.6 μg.ml-1), in the fifth instar were extracted the haemolymph and measured the number of haemocytes, total protein and phenoloxidase activity (PO). Neonate offspring of those individuals were inoculated with 0 and 40 μg.ml-1 of HD-73 and again was quantified the same immune components in fifth instar larvae, including antibacteriana activity. In addition, biological parameters were observed in these tests. In the evaluation of Cry1Ac impacts on virus infectivity in S. frugiperda, neonate were exposed to HD-73 (0, 10, 40 and 80 μg.ml-1) until the end of the third instar and early of the fourth instar was inoculated with viruses (0, 103 and 104 OB.larvae-1). For this assay was evaluated larval weight (4 DAE), mortality, number of OB/caterpillar and subsequently, virulence test (LC50). Spodoptera cosmioides, Spodoptera eridania, S. frugiperda, Chrysodeixis includens and Rachiplusia nu caterpillars were simultaneously or sequentially exposed to entomopathogens, HD-73, M. rileyi and their viruses, and record mortality and biological parameters of these interactions. The sublethal concentrations of HD-73 did not cause changes in the immune system of the parental, as well as there was no evidence for acquired immunity in the offspring. Sublethal concentration of HD-73 affected the biological components of S. frugiperda, providing lower larval and pupal weight, reduced fecundity and egg viability. HD-73 proved lower OB yield/caterpillar and lower virulence of the virus multiplied in caterpillars prior exposed to 10 μg.ml-1. The interactions did not affect the biological parameters of these noctuids. In most cases was observed negative effect in the interactions between HD-73 and viruses, but may be promising simultaneous inoculation of HD-73 and M. rileyi to control S. eridania and S. frugiperda. Sublethal concentrations of HD-73 did not provide larger mortality of Plusiinae in interactions with M. rileyi and viruses, except for HD-73+ M. rileyi that had positive and negative effects on C. includens.